Islamic theology, philosophy and law : debating Ibn Taymiyya and Ibn Qayyim al-Jawziyya - Kokoschka, Alina; Krawietz, Birgit; Tamer, Georges (Studien zur Geschichte und Kultur des islamischen Orients ;, 2013)
Considering their widespread and highly controversial legacy, Ibn Taymiyya and his foremost disciple, Ibn Qayyim al-Jawziyya, arguably belong to the most influential figures of Islamic thought. The contributions within this volume address significant philosophical and theological themes in their work and examine their impact in the areas of Islamic law, Sufism and contemporary revival movements in Middle Eastern, Indian, and Southeast Asian Muslim societies.